Biofuels policies that have encouraged their production and use: An international perspective. (December 2020) - Ebadian, Mahmood; van Dyk, Susan; McMillan, James D.; Saddler, Jack
Abstract: This study evaluated the effectiveness of technology-push and market-pull policies in encouraging the production and use of biofuels in 15 countries including major biofuels producers. Biofuels production and consumption data for the 12-year period of 2006-2017 showed that in most of the surveyed countries, biofuels policies played an important role in developing and growing regional and national biofuels markets. Blending mandates continue to be the main market-pull policy used to create and expand biofuels markets. Countries with a mixture of market-pull and technology-push policy instruments have been most successful at increasing biofuels production and use and also developing and deploying less mature advanced biofuels. Most policies have primarily promoted the production and use of biofuels for road transport with key long-distance transport sectors (aviation and shipping) drawing less policy attention despite being significant fuel consumers and carbon emitters. While many older policies were originally developed to promote energy security, more recent policies, such as low carbon fuel standard, have reduction in the carbon intensity of transportation fuels as a primary goal. While policies have been essential in promoting the on-going growth of biofuels, they have not been sufficient to drive the level of development needed to decarbonize the transport sector. Highlights: Biofuels policies have played an important role in developing biofuel markets. Combinations of demand-pull and technology-push policies has been most successful. Policies have primarily promoted the production and use of road transport biofuels. Biofuel blending mandates are the primary biofuels policies use by most countries. There is a shift from blending mandates to carbon-intensity type biofuel policies.